The rhetoric of comedy: exploring the language and humor styles of Filipino stand-up comedians - Joser, Joan Recca; Dedace, Jean Rose; Daclizon, Karen; Salvaña, Prince Lejard; Nacionales, Joseph; Claridad, Norberto (Journal of Language and Pragmatics Studies, 2023)
Stand-up comedy is an act in which a certain person performs to make people laugh with the intention of appealing to them. It illustrates various language and humor styles that are used by comedians in performing; these styles vary depending on the audience, place, and theme of the event and are unique to each performer. This study aims to provide information regarding the specific approach that Filipino stand-up comedians used during their performances and how effective it was for the delivery and reception of humor. This study employed a qualitative research design using interpretative phenomenological analysis as the specific approach with which it is concerned in exploring experiences in their own terms (Smith et al, 2009). The study also uses thematic analysis approach as proposed by Braune and Clarke which revealed two themes under language styles utilized by stand-up comedians (1) incorporating language based on the audience (2) use of colloquial words and phrases. Three themes under humor styles utilized by stand-up comedians are (1) audience-centric performance, (2) observational comedy, (3) improvisational comedy. Also, three themes underlie the effectiveness of using language and humor styles: (1) importance of building connections, (2) extensive influences of endeavoring to be funny and, (3) enhancing audience satisfaction.